Cerebrospinal fluid levels of proenkephalin and prodynorphin are differentially altered in Huntington’s and Parkinson’s disease - Barschke, Peggy; Abu-Rumeileh, Samir; Al Shweiki, M. H. D. Rami; Barba, Lorenzo; Paolini Paoletti, Federico; Oeckl, Patrick; Steinacker, Petra; Halbgebauer, Steffen; Gaetani, Lorenzo; Lewerenz, Jan; Ludolph, Albert Christian; Landwehrmeyer, Georg Bernhard; et al. (Journal of neurology, 2022)
Background Proenkephalin (PENK) and prodynorphin (PDYN) are peptides mainly produced by the striatal medium spiny projection neurons (MSNs) under dopaminergic signaling. Therefore, they may represent candidate biomarkers in Huntington’s disease (HD) and Parkinson’s disease (PD), two neurodegenerative diseases characterized by striatal atrophy and/or dysfunction. Methods Using an in-house established liquid chromatography−tandem mass spectrometry (LC–MS/MS) method in multiple reaction monitoring mode (MRM) we measured cerebrospinal fluid (CSF) levels of PENK- and PDYN- derived peptides in patients with HD ( n = 47), PD ( n = 61), Alzheimer’s disease ( n = 11), amyotrophic lateral sclerosis ( n = 14) and in 92 control subjects. Moreover, we investigated the possible associations between biomarkers and disease severity scales in HD and PD and the effect of dopaminergic therapy on biomarker levels in PD. Results In HD, CSF PENK- and PDYN-derived peptide levels were significantly decreased compared to all other groups and were associated with disease severity scores. In PD, both biomarkers were within the normal range, but higher PDYN levels were found in dopamine-treated compared to untreated patients. In PD, both CSF PENK and PDYN did not correlate with clinical severity scales. Conclusions CSF PENK- and PDYN-derived peptides appeared to be promising pathogenetic and disease severity markers in HD, reflecting the ongoing striatal neurodegeneration along with the loss of MSNs. In PD patients, CSF PDYN showed a limitative role as a possible pharmacodynamic marker during dopaminergic therapy, but further investigations are needed.